The Social Glue: Humor and Open-Minded Thinking as Predictors of Friendship Quality in Migrant Students - Nuraeni, Cindy; N. Kardinah; Nurany, Putri Nabhani (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: For migrant university students, the transition to a new environment presents significant risks of social isolation, making high-quality friendships a critical buffer for psychological well-being. However, the internal cognitive and behavioral traits that drive these social bonds remain under-explored. This study examines the influence of a sense of humor and actively open-minded thinking (AOT) on friendship quality among undergraduate migrant students in Bandung (N=289). Using multiple linear regression analysis, we demonstrate that humor and AOT are significant predictors of social success, accounting for 25.9% of the variance in friendship quality. Our findings suggest that the ability to process diverse perspectives (AOT) and navigate social tension (humor) are essential competencies for building supportive networks. These results provide a framework for university counseling programs to enhance student resilience through targeted social-cognitive interventions. Key Words: Humor, Open-minded thinking, friendship quality, undergraduate migrant students